Advances in Minimally Invasive Surgery and Therapy for Spine and Nerves - Alexandre, Alberto; Masini, Marcos; Menchetti, Pier Paolo Maria; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2011)
Radiologists, orthopedic and neurological surgeons present the different minimally invasive methods. Peripheral nerve problems and problems concerning differential diagnosis in special situations such as between radicular and peripheral nerve trunk lesions are discussed, pinpointing the significance of different diagnostic tools. Minimally invasive techniques, utilized nowadays to minimize bone demolition, scarring and risk of recurrence are analyzed. Microdiscectomy is compared with the results of intradiscal techniques, and new methods are discussed facing problems such as epidural fibrotisation, microinstability, osteoporotic or neoplastic or posttraumatic vertebral lesions.
Keywords: Medicine; Neurosurgery; Orthopedic surgery; Medicine & Public Health; Neurosurgery; Surgical Orthopedics